2001
DOI: 10.1046/j.1365-3083.2001.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subcutaneous IL‐2 Therapy on Telomere Lengths in PBMC in HIV‐Infected Patients

Abstract: In this study we investigated the effect of interleukin-2 (IL-2) on mean terminal restriction fragment (TRF) lengths in peripheral blood mononuclear cells (PBMC). Ten human immunodeficiency virus (HIV)-infected individuals were included and IL-2 was administered subcutaneously with 3 Â 10 6 IU three times a week for 24 weeks. Mean TRF length was decreased on average by 267 bp at week 4 (P 0.03) and 286 bp at week 8 (P 0.09). Individual TRF changes at weeks 12, 16, 20 and 24 were highly variable. However, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…8 The coexistence of enhanced myelopoiesis (as revealed by increased PMN counts) and defects in T cell counts favors the hypothesis that IL-2 and GM-CSF expand post-PBSCT myelopoiesis at the expense of T cell regeneration through a mechanism of in vivo stem cell competition. Additionally, a recent report by Aladdin et al 33 showed that subcutaneous IL-2 administration shortens telomere length of peripheral blood mononuclear cells of individuals infected with HIV with selective expansion of memory T cells and concomitant reduction of both CD4 ϩ CD45RA ϩ and CD8 ϩ CD45RA ϩ naive lymphocytes, which is highly reminiscent of our present observations. Finally, the small size of our patient sample, the short follow up of G-CSF/EPO plus IL-2 series and the lack of relevant differences in the rate of early and late relapse between our distinct patient series prevent any preliminary conclusion on the clinical role of post-PBSCT IL-2 addition to G-CSF/EPO regimen.…”
Section: Discussionsupporting
confidence: 89%
“…8 The coexistence of enhanced myelopoiesis (as revealed by increased PMN counts) and defects in T cell counts favors the hypothesis that IL-2 and GM-CSF expand post-PBSCT myelopoiesis at the expense of T cell regeneration through a mechanism of in vivo stem cell competition. Additionally, a recent report by Aladdin et al 33 showed that subcutaneous IL-2 administration shortens telomere length of peripheral blood mononuclear cells of individuals infected with HIV with selective expansion of memory T cells and concomitant reduction of both CD4 ϩ CD45RA ϩ and CD8 ϩ CD45RA ϩ naive lymphocytes, which is highly reminiscent of our present observations. Finally, the small size of our patient sample, the short follow up of G-CSF/EPO plus IL-2 series and the lack of relevant differences in the rate of early and late relapse between our distinct patient series prevent any preliminary conclusion on the clinical role of post-PBSCT IL-2 addition to G-CSF/EPO regimen.…”
Section: Discussionsupporting
confidence: 89%
“…IL-2 administration increased the number of LCMV-specific CD8 1 T cells and resulted in decreased viral burden, indicating therapeutic potential of IL-2 for chronic viral infections. In addition, many clinical trials of IL-2 administration in HIVinfected patients have been performed, although the main purpose of these trials is to maintain or increase CD4 1 T-cell numbers rather than expand virus-specific CD8 1 T-cell numbers (195)(196)(197)(198). Through these trials, IL-2 therapy was shown to significantly increase and sustain CD4 1 T-cell counts in a large majority of patients compared with patients who are treated with antiretroviral drugs alone ( Table 2).…”
Section: Siv Zmentioning
confidence: 99%